2023
DOI: 10.3389/fpubh.2022.1059346
|View full text |Cite
|
Sign up to set email alerts
|

The impact of internet use on old-age support patterns of middle-aged and older adults

Abstract: BackgroundThe trend towards low fertility and low mortality is prominant worldwide. The accelerating ageing and the pressure on public pensions are making the “dependent pattern of old-age support”, which relies on family and government, unsustainable. It is urgent for people to change their mindset about ageing and to develop a sense of “relying on themselves for oldage support”.MethodsThis study incorporates the commercial pension insurance, formal care and the attitude towards independent old-age support pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…Finally, considering the effect of the potential time trend, following Li et al ( 39 ) and Wang et al ( 40 ), the time trend term is included in the regression and the results are as in column (7) of Table 3 . After controlling for the potential time trend factor, the results remain significant at the 1% level and the correlation coefficients do not change significantly, thus further validating the theoretical assumptions of the paper and the robustness of the data results.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, considering the effect of the potential time trend, following Li et al ( 39 ) and Wang et al ( 40 ), the time trend term is included in the regression and the results are as in column (7) of Table 3 . After controlling for the potential time trend factor, the results remain significant at the 1% level and the correlation coefficients do not change significantly, thus further validating the theoretical assumptions of the paper and the robustness of the data results.…”
Section: Resultsmentioning
confidence: 99%
“…Their study underscored the evolving landscape of pension insurance consumption, propelled by the digital revolution and its implications for insurance industry practices. [9] Collectively, these studies offer a kaleidoscopic view of the multifaceted dynamics and implications of commercial pension insurance across diverse contexts. By enriching our understanding of consumer perspectives and drivers, they serve as invaluable compasses guiding policy and practice within the insurance domain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The connection between social capital and health literacy has been the subject of a few studies (38,39), and some scholars suggested that cultural capital may have an impact on social capital (20), but there is no empirical research to clarify the link between cultural capital and health literacy among community residents. Existing studies only emphasize the importance of cultural capital on health literacy, which only briefly discussed the connection between these two factors without examining the mechanisms behind the connected pathways.…”
Section: Introductionmentioning
confidence: 99%